Clinicopathological and Prognostic Value of USP22 Expression in Gastric Cancer: A Systematic Review and Meta-Analysis and Database Validation - Wang, Yuhang; Jia, Zirui; Gao, Jiacheng; Zhou, Tingting; Zhang, Xiangwen; Zu, Guo (Frontiers in Surgery, 2022)
Background: It has been reported there is a correlation between the level of ubiquitin-specific protease 22 (USP22) and the clinicopathological parameters and prognosis of gastric cancer (GC) patients, but the conclusions are inconsistent. Hence, a meta-analysis must be conducted to clarify the relationship between USP22 expression and clinicopathological and prognostic value of GC patients to provide more accurate evidence. Methods: According to the pre-determined selection criteria, systematic file retrieval was performed. The hazard ratio (HR) or odds ratio (OR) and its 95% confidence interval (CI) were used to evaluate the relationship between USP22 expression and clinicopathological and prognostic value of GC patients. Results: In total of 802 patients with GC were finally included in 6 studies. The pooled results demonstrated that the expression of USP22 was significantly increased in GC tissues compared with control tissues (OR = 9.947, 95% CI = 6.074–16.291, P = 0.000), and USP22 expression was related to lymph node metastasis (OR = 2.415, 95% CI = 1.082, P = 0.031), distant metastasis (OR = 3.956, 95% CI = 1.365–11.464, P =0.011) and TNM stage (OR = 2.973, 95% CI = 1.153–7.666, P = 0.024). Nevertheless, expression of USP22 was not correlated with gender (OR = 1.202, 95%CI = 0.877–1.648, P = 0.253), age (OR = 1.090, 95%CI = 0.811–1.466, P = 0.568), tumors size (OR = 0.693,95% CI = 0.348–1.380, P = 0.297), tumor differentiation (OR = 1.830, 95%CI = 0.948–3.531, P = 0.072) and depth of invasion (OR = 2.320, 95% CI = 0.684–7.871, P = 0.177). Moreover, High expression of USP22 predicted a poor overall survival (OS) in GC patients (HR = 2.012, 95% CI =1.522–2.658, P = 0.000). The database of Kaplan-Meier plotter confirmed that high expression of USP22 was correlated with poor prognostic in GC patients (HR = 1.41, 95% CI = 1.18–1.68, P < 0.01). Conclusion: USP22 overexpression in GC tissues is positively related with lymph node metastasis, distant metastasis, TNM stage and indicated poor clinical outcome of GC patients, but it is not associated with age, gender, depth of invasion, tumor differentiation and tumor size of GC patients.